Electrochemical Biogas Upgrading: Energy, Environmental, Economic, and Engineering Considerations - Aishwarya Rani; Suraj Negi; Yu‐Ning Chen; Cheng‐Hsiu Yu; Shu‐Yuan Pan (GCB Bioenergy)
ABSTRACT Biogas, a renewable energy source produced from the anaerobic digestion of biomass and/or organic residues, contains a mixture of methane (CH4) and carbon dioxide (CO2). To be used as a fuel, biogas must be upgraded to increase its CH4 content to over 90%. Traditional upgrading methods, such as amine scrubbing and membrane separation, are energy‐intensive, costly, and environmentally burdensome. This study explores the potential of electrochemical technologies as sustainable alternatives for biogas upgrading from the aspects of energy, environment, economics, and engineering. Recent advances in promising electrochemical approaches including pretreatment, microbial conversion enhancement, CO2 capture, CO2 reduction reactions, and methanation are first reviewed. The performance of these approaches is then systematically compared based on operational characteristics and efficiency metrics. Our findings indicate that microbial and bioelectrochemical systems can achieve CH4 purities over 92%. Also, electrochemical technologies offer > 99.9% hydrogen sulfide removal (desulfurization). State‐of‐the‐art electrochemical CO2 reduction technologies demonstrate Faradaic efficiencies generally 50%–80%, with the selectivity of CH4 up to 99.7%. From the environmental aspect, integrating renewable electricity into microbial, electrochemical (or ‐based), and bioelectrochemical upgrading systems yields roughly 10%–74% life‐cycle GHG reductions relative to conventional fossil‐energy pathways, with certain renewable power‐to‐methane configurations achieving net‐negative emissions. Lastly, this study identifies several priority research directions, such as (1) advanced catalyst and electrode development, (2) system integrations with air pollutant control facilities, (3) life‐cycle environmental and techno‐economic assessment, and (4) digestate valorization for multiple product ecosystems. Electrochemical approaches offer a promising path toward clean, efficient, and decentralized biogas utilization, contributing to global decarbonization and energy transition goals toward a circular bioeconomy.